PCAT19: the role in cancer pathogenesis and beyond - Haijun Hu; Hongliang Luo; Ziqing Deng (Frontiers in Cell and Developmental Biology)
PCAT19, a long non-coding RNA, has attracted considerable attention due to its diverse roles in various malignancies. This work compiles current research on PCAT19’s involvement in cancer pathogenesis and progression. Abnormal expression of PCAT19 has been observed in various cancers, and its correlation with clinical features and prognosis positions it as a promising prognostic biomarker. Additionally, its ability to effectively differentiate between tumor and normal tissues suggests significant diagnostic value. PCAT19 exhibits a dual nature, functioning either as an oncogene or a tumor suppressor, depending on the cancer type. It is implicated in a range of tumor-related activities, including cell proliferation, apoptosis, invasion, migration, metabolism, as well as tumor growth and metastasis. PCAT19 acts as a competing endogenous RNA (ceRNA) or interacts with proteins to regulate critical cancer-related pathways, such as MELK signaling, p53 signaling, and cell cycle pathways. Furthermore, emerging evidence suggests that PCAT19 plays a role in the modulation of neuropathic pain, adding complexity to its functional repertoire. By exploring the molecular mechanisms and pathways associated with PCAT19, we aim to provide a comprehensive understanding of its multifaceted roles in human health and disease, highlighting its potential as a therapeutic target for cancer and pain management.